Harmful Effects of the Dermal Intake of Commercial Formulations Containing Chlorpyrifos, 2,4-D, and Glyphosate on the Common Toad Rhinella arenarum (Anura: Bufonidae) - Lajmanovich, Rafael Carlos (2015)
Amphibians have complex life cycles with aquatic and terrestrial life and uncovered skins; therefore, they are exposed to chemical contamination, where dermal exposure is a significant route for pesticide uptake in both habitats. In this study, measurements in blood samples such as levels of butyrylcholinesterase (BChE), carboxylesterase (CbE), glutathione Stransferases (GST), thiobarbituric acid reactive substances (TBARS), modified alkaline comet assay (ACA) for detection of oxidized bases (FPG and Endo III sites), as well as the ratio of heterophils and lymphocytes (H/L), were evaluated as non-destructive biomarkers to monitor dermal pesticide exposure in male toads of Rhinella arenarum. Toads were exposed to a solution containing a nominal concentration of commercial formulations of the insecticide chlorpyrifos (CPF, 10 mg/L), and herbicides 2,4-D and glyphosate (GLY) (20 mg/L, respectively). After 48 h of exposure, the levels of plasma B-sterases (BChE and CbE) were inhibited (55 and 43 %, respectively) in toads exposed to CPF. Also, the activity of GST was inducted for dermal exposure to 2,4-D, as well as the levels of TBARS due to CPF exposure. Besides this, CPF and 2,4-D exposure induced oxidative DNA damage, and the H/L ratio decreased for the both herbicide exposures. Our results showed that exposure via dermal uptake to CPF, 2,4-D, and GLY in the common toad R. arenarum induced neurotoxicity, oxidative stress, and immunological depression. Thus, some blood biomarkers employed in our study (B-esterases, GST, levels of TBARS, ACA, and H/L ratio) might be used as predictors in health and ecological risk assessment of amphibian populations exposed to OP insecticides and herbicides.